New Records of Hippolytid Shrimps, Lebbeus speciosus and Lebbeus comanthi (Crustacea: Decapoda: Caridea) from the East Sea, Korea - Chu Lee; Hyun Sook Ko; Kyu Hyun Lee (Animal Systematics, Evolution and Diversity, 2013)
Two species of the hippolytid shrimps, Lebbeus speciosus and Lebbeus comanthi, are described and illustrated for the first time in Korea. They were collected from the East Sea. Lebbeus speciosus was found in a scallop farm of Jumunjin, Gangneung, and L. comanthi associated with crinoids, was found in Gampo, Gyeongju. The difference between these two related species is in the number of dorsal teeth of the rostrum, five teeth in L. speciosus and a single tooth in L. comanthi. The Korean Lebbeus species has increased to 6 species by the present report. They are L. grandimana, L. polaris, L. unalaskensis, L. groenlandicus, L. speciosus, and L. comanthi.